Effects Of Delayed Evaporation In Cellulose Acetate Membrane Preparation To Separate Co2/Ch4 At Low Pressure - Adiwar Adiwar (Testing Center for Oil and Gas LEMIGAS, 2009)
The effect of delayed evaporation rate on CO2/CH4 selectivity was investigated on cellulose acetate based membrane in composition of cellulose acetate and acetone (CA+ACE), cellulose acetate, acetone and formamide (CA+ACE+F) and cellulose acetate, acetone, formamide and polyethylene glycol 400 (CA+ACE+F+PEG). Delayed evaporation was carried out in acetone saturated air. The study shows that the presence of PEG in membrane composition gives a probability for the membrane to be used and kept in dry state. Evaporation time at standard evaporation rate for membrane composition CA+ACE+F andd CA+ACE+F+PEG to get better selectivity is not less than 60 seconds. SEM shows that macrovoids in membrane prepared by delayed evaporation rate compared to those prepared by standard evaporation are smaller in size but higher in numbers.Effects of 60 seconds of delayed evaporation rate on membrane selectivity and permeability is about the same with the effects of 15 seconds of standard evaporation. It brought abourt, in turn, a thought, that the effects of 8 seconds evaporation in spineret on hollow fibre selectivity and permeability can be increased by increasing evaporation rate.